Approach Based on Data Mining for Exploring the Hierarchical Decision-Making Rules between the Generation of Transnational Immigrants’ Sense of Place in Religious Spaces and Perception of the Environment - Mei, Lin (Religions, 2022)
The generation of transnational immigrants’ sense of place in the religious space of the places they move to can protect and promote their integration into the local society by shaping a sense of place identity and belonging through the positive effects of human-environment interaction and the strengthening of the religious beliefs of the migrant community. China is in a period of economic transition in the post-reform and opening-up era, and has become one of the key testing grounds for observing and summarizing the internationally mobile population. However, there is a relative lack of empirical studies at the micro level. It is unclear how the socio-cultural and physical environment in religious places in urban China influences and leads to the construction of identity and local meaning among transnational immigrants. This study uses the Chapelle Notre-Dame de Lourdes in Guangzhou as an empirical case study, distributes questionnaires to foreign immigrants, and applies data mining approaches to analyze the data. The study also explores the knowledge of the rules related to the religious atmosphere perceived by the immigrants in this environment and their place identity, place attachment and place dependency. This study found that a place of worship that supports frequent and interactive ritual activities and provides a natural, harmonious, and solemn green landscape environment can effectively promote foreign immigrants’ sense of local attachment to the place of worship. The establishment of emotional relationships between religious places and foreign immigrants depends on the immigrant community’s satisfaction with the local physical environment and its perceived judgment. The speed of attachment and identity building depends on the light and shadow environment, architectural colors and materials, natural vegetation and other environmental elements related to the creation of the religious atmosphere that people perceive in the place. For Guangzhou City, which is in the process of globalization and transition to "multicultural services", this study provides local policy makers with a critical reference for decision making on the creation and renewal of religious places in immigrant communities. The provision of more relevant production and living services for the internationally mobile population, and the enhancement of the local identity of the internationally mobile population to the place of migration are directions that academia and society need to explore together in the future.